(untitled) (Asian Journal of Agriculture, 2018)
Abstract. Sumoharjo, Ma’ruf M, Budiarto I. 2018.Biomass production of Azolla microphylla as biofilter in a recirculating aquaculture system. Asian J Agric 2: 14-19. This study utilized macrophyte (Azolla microphylla Kaulf.) as a biofilter and investigated that biomass produced in an aquaculture system could potentially be an alternative feed. This experiment was aimed to determine the Azolla microphylla growth rate and its efficiency in removing ammonia from a simple recirculating aquaculture system. The experimental units were set up in three different water flows, i.e. 3 lpm, 5 lpm, and 7 lpm onto the three different geometrically baseboards of Tilapia (Oreochromis niloticus) growing tanks (prism, rectangular and limas). The results showed that water flow did not give significant effect(P < 0.10) on the growth rate of Azolla. The lower water flow (3 lpm) resulted in the highest ammonia biofiltration efficiency, which can remove ammonia up to 32.2±3.0% of the total NH3-N and NH4+-N (TAN).